ANALISIS MEKANISME PEMBIAYAAN DANA TALANGAN HAJI PADA PT. BANK BNI SYARIAH KANTOR CABANG MEDAN - Syahrul Amsari (Ekonomi Islam, 2021)
The background of this Financing bailout Hajj Product is the occurrence of a long queue of Jemaah hajj candidates. Thus people have to wait long to be able to perform the pilgrimage.Therefore to meet the needs of the community, so PT Bank BNI Syariah Branch Office Medan provides product financing bailouts in order to facilitate the pilgrimage bailout for prospective pilgrims to obtain Haj chair seat. The purpose of this study to be able to explain the implementation and financing mechanisms bailout funds Haj in helping customers to get the chair seat Haj, as well as contract-contract, knowing what is on pilgrimage financing bailouts in Bank BNI Syariah Branch Office Medan. The method used in this study is a qualitative research study of literature and interview data collection and documentation. Then described from the data that have been obtained are analyzed and conclusions are drawn. The results can be concluded that the Operational Management Product Bailout Financing Hajj at Bank BNI Syariah Branch Office Medan implements petition financing mechanisms. Principles used to use Qardh and Ijarah contract. Qardh scheme used for the bailout loans, and taking advantage of Ijarah or wages for services (Ujrah). Keywords: Finance, Qardh, Ijarah, Hajj bailouts, Bank BNI Syariah Branch Medan.